Eksistensi Penglipuran Village Festival IX Sebagai Pengenalan Community Attachment Desa Penglipuran Kabupaten Bangli - Swandewi, Ni Kadek; Swandewi, I Gede; Asmarani, I Gusti Ayu Ratih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2023)
Festivals can be interpreted as a celebration by the local community which is part of the arts and performances and includes other activities such as performing music concerts. The 9th Penglipuran Village Festival presents a variety of unique and interesting things, not only limited to performances but more highlighting the socio-cultural wisdom that characterizes the local community. In the Penglipuran Village community, various cultural and ritual events are carried out through a pattern of togetherness or mutual cooperation which involves the entire community including event Penglipuran Village Festival. This research was conducted using observation methods and in-depth interviews with managers event Penglipuran Village Festival which was held for the ninth time. With the theme